2011
DOI: 10.5505/1304.7361.2011.82473
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alcohol Poisoning in Bulgarian Adolescents

Abstract: ÖZET Amaç Çalışmanın amacı, Bulgar ergenlerinde görülen akut alkol zehirlenmelerinin mediko-sosyal özelliklerini analiz etmektir. Gereç ve YöntemÇalışma kapsamında [2006][2007][2008] SUMMARY ObjectivesTo analyze the medico-social characteristics of acute alcohol poisoning in Bulgarian adolescents. MethodsWe studied patients under 18 years old with acute alcohol poisoning who were hospitalized during the period 2006-2008. Data were retrieved from hospital records. The initial blood ethanol level was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…They also pose the highest health risk due to their unknown content. Our analysis has shown that male adolescents were more likely to use NPSs, as confirmed in both the Polish and global literature [ 17 , 18 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 82%
“…They also pose the highest health risk due to their unknown content. Our analysis has shown that male adolescents were more likely to use NPSs, as confirmed in both the Polish and global literature [ 17 , 18 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, Sierosławski showed in his survey that beer is the most popular alcohol among male adolescents (23) . It can be therefore concluded that paediatric admissions due to less potent alcohol (beer) are less common than those associated with consuming strong liquors, such as vodka (10,17,24) . Consumption of alcohol in large quantities, especially those that exceed the threshold of intoxication, is particularly dangerous, primarily for the health of young people using psychoactive substances, but also for public order.…”
Section: Discussionmentioning
confidence: 99%